THE METHOD OF DEVELOPING LEXICAL COMPETENCE OF STUDENTS IN THE PROFESSIONAL FIELD - Elmirzaeva O.N. (Zeta Repository, 2023)
Given article deals with the peculiarities of teaching English as a specific and target needs. Language learning does not only involve acquiring grammatical structure but also its function. It is important for agriculture students to be able to present their ideas, exchange their opinions or follow agricultural developments all over the world. Most universities in Uzbekistan have been offering ESP courses besides the general English lessons to boost their confidence in this field.